Critical Success Factors of Lean Implementation in the Construction Industry - Demirkesen, Sevilay; Bayhan, Hasan Gokberk (IEEE-Inst Electrical Electronics Engineers Inc, 2022)
Lean implementation aims to maximize customer satisfaction while minimizing waste. However, the Lean philosophy has not yet been well understood in the construction industry due to complex and dynamic nature of construction projects. Even though Lean efforts in construction have recently gained popularity, there are still problems with the implementation processes. Therefore, it is essential to identify critical success factors (CSFs) in Lean implementation for conducting projects more effectively. Due to lack of studies in revealing CSFs in Lean implementation and the need for an up-to-date Lean implementation roadmap, this article provides an extensive set of CSFs for construction practitioners to benefit in their projects. Within this context, 27 variables were identified through an in-depth literature review. Moreover, a survey is designed and given to Lean practitioners to rank the variables based on their importance. The findings of the survey indicate that management commitment is ranked as the most important driver of Lean implementation, whereas the supportive nature of governmental regulations in Lean is ranked as the least important. A factor analysis of CSFs result in six factor groups, namely motivational factors, project factors, strategic and policy factors, company factors, technical factors, and workforce and resource factors.
Keywords: Construction industry; Companies; Tools; Lean production; Productivity; Critical success factors (CSFs); factor analysis; lean construction; lean construction tools; lean implementation; lean implementation techniques